The effect of intergroup competition outcome on ingroup cooperation: insights from the male warrior hypothesis - Belinchón, Montserrat; Polo, Pablo; Rodriguez-Sickert, Carlos; Figueroa, Oriana; Valenzuela, Nohelia; Pavez, Paula; Muñoz-Reyes, José Antonio (Frontiers in Psychology, 2024)
The Male Warrior Hypothesis (MWH) proposes that sex-specific selective pressures have promoted male cooperation with the ingroup members to outcompete rival groups. However, intergroup conflicts do not occur in isolation and the outcomes of previous competitions may influence group cooperativeness. Since this phenomenon is not well understood, we aimed to shed light on the effect of previous competition outcome on later cooperative behavior under intergroup conflicts. Based on the MWH, we hypothesized that repeated contests between groups could enhance ingroup cooperation, regardless of the outcome of the previous contest because status is at risk, but when competition is not present, participants would move to the symmetric equilibria. To test this hypothesis, we recruited 246 individuals organized in groups of 6 and measured cooperation using a threshold public good game over two rounds, manipulating the outcome in the first round to create groups of winners and losers. Our results show that intergroup conflict scenarios promoted cooperation in both victory and defeat conditions, whereas, in the control scenario only losers increased their cooperation. We argue that winners under the presence of an external threat may enhance in-group cooperation in order to assure their status; whereas, losers may be attempting to regain it.